At last! Posted another problem after 5 weeks

Algebra Level 3

If r 1 , r 2 , r 3 , r 4 r_{1}, r_{2}, r_{3}, r_{4} are the roots of the equation 4 x 4 3 x 3 x 2 + 2 x 6 = 0 4x^{4}-3x^{3}-x^{2}+2x-6=0 , what is the value of 1 r 1 + 1 r 2 + 1 r 3 + 1 r 4 \frac{1}{r_{1}}+\frac{1}{r_{2}}+\frac{1}{r_{3}}+\frac{1}{r_4} ?

1 3 \frac{1}{3} 1 4 \frac{1}{4} 1 5 \frac{1}{5} 1 2 \frac{1}{2}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Daniel Liu
Jun 18, 2015

If the original polynomial is P ( x ) = 4 x 4 3 x 3 x 2 + 2 x 6 P(x)=4x^4-3x^3-x^2+2x-6 with roots r 1 , r 2 , r 3 , r 4 r_1,r_2,r_3,r_4 then the polynomial Q ( x ) = x 4 P ( 1 x ) = 6 x 4 + 2 x 3 x 2 3 x + 4 Q(x)=x^4P\left(\dfrac{1}{x}\right)=-6x^4+2x^3-x^2-3x+4 has roots 1 r 1 , 1 r 2 , 1 r 3 , 1 r 4 \dfrac{1}{r_1}, \dfrac{1}{r_2}, \dfrac{1}{r_3}, \dfrac{1}{r_4} .

By vietas, we have 1 r 1 + 1 r 2 + 1 r 3 + 1 r 4 = 2 6 = 1 3 \dfrac{1}{r_1}+ \dfrac{1}{r_2}+ \dfrac{1}{r_3}+ \dfrac{1}{r_4}=-\dfrac{2}{-6}=\boxed{\dfrac{1}{3}}

Nihar Mahajan
Jun 18, 2015

By Vieta's formula we have :

r 1 r 2 r 3 + r 1 r 2 r 4 + r 1 r 3 r 4 + r 2 r 3 r 4 = 2 r 1 r 2 r 3 r 4 = 6 1 r 1 + 1 r 2 + 1 r 3 + 1 r 4 = r 1 r 2 r 3 + r 1 r 2 r 4 + r 1 r 3 r 4 + r 2 r 3 r 4 r 1 r 2 r 3 r 4 = 2 6 = 1 3 \large{r_1r_2r_3+r_1r_2r_4+r_1r_3r_4+r_2r_3r_4 = -2 \\ r_1r_2r_3r_4= -6 \\ \Rightarrow \dfrac{1}{r_1}+\dfrac{1}{r_2}+\dfrac{1}{r_3}+\dfrac{1}{r_4}=\dfrac{r_1r_2r_3+r_1r_2r_4+r_1r_3r_4+r_2r_3r_4 }{r_1r_2r_3r_4} \\ = \dfrac{-2}{-6} = \boxed{\dfrac{1}{3}}}

C O R R E C T ! \large{CORRECT !}

This was a free 100 points

Vaibhav Prasad - 5 years, 12 months ago

It was quite easy.. well.. I used a similar approach

Rishabh Tripathi - 5 years, 12 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...